The Effect of Transformational Leadership on Employee Performance Through Job Satisfaction and Organizational Commitment - Nastavia Putri; Lista Meria (Pandawan Sejahtera Indonesia, 2022)
This study aims to examine and examine the effect of transformational Leadership on employee performance through job satisfaction and organizational commitment. Transformational Leadership is an exogenous variable, Employee Performance as an endogenous variable, and Organizational Commitment and Job Satisfaction are mediating variables. This research was conducted on leaders and employees in food & beverage companies found in Jakarta. The background of this research is the leadership style in empowering employees, which aims to improve the quality of professionalism and performance of employees in carrying out their duties and functions optimally. Things that must be considered in food & beverage companies such as Transformational Leadership, Employee Performance, Organizational Commitment, and Job Satisfaction. This study uses samples taken by purposive sampling method, using the Hair calculation method for as many as 135 respondents. The analytical method used is the Structural Equation Model (SEM), and uses Partial Least Square (PLS) to test the strength of direct and indirect relationships between various variables. The results of this study indicate that Transformational Leadership affects Job Satisfaction, Transformational Leadership has an effect on Organizational Commitment, Transformational Leadership has an effect on Employee Performance, Job Satisfaction has an impact on Employee Performance, Organizational Commitment has an effect on Employee Performance, Transformational Leadership has an effect on Employee Performance through Job Satisfaction, Transformational Leadership has an impact on Employee Performance through Organizational Commitment.